Critical Consciousness in Sport Scale (CCSS): development and initial psychometrics properties - Peixoto, Evandro M.; Camiré, Martin; Romano, Amanda R. (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background Critical consciousness refers to the ability to recognize and analyze the oppressive forces in society and to act against them. Researchers have emphasized that sport has the potential to help athletes develop their critical consciousness regarding the forces that shape society, as well as the systems of privilege and deprivation that influence access to sport. Objective The present study describes the development of the critical consciousness in sport scale, offering initial validity evidence based on test content, internal structure, relations with other variables, and reliability. Methods An initial set of 50 items was develop and reviewed by expert judges who assessed the clarity, practical relevance, and theoretical adequacy of the items using the content validity coefficient (CVC). To investigate the internal structure of the CCSS, factor retention methods such as parallel analysis and exploratory graph analysis were employed, followed by an exploratory factor analysis (EFA), along with an assessment of the internal consistency of the factors. Validity evidence based on relations with other variables was estimated using Pearson correlations. The sample was comprised of 263 Brazilian psychology and physical education students (mean age: 26.95 ± 9.69; 70.02% women). Results Factor retention methods that included parallel analysis, exploratory graph analysis, and a categorical exploratory factor analysis demonstrated a three-dimensional structure comprised of 36 items, as theoretically hypothesized, with desirable internal consistency indices (ω = 0.868, 0.906, and 0.924, respectively). A brief version of the instrument is also presented, which adequately reproduced the psychometric properties of the initial version. Correlations with measurements of social justice and anti-racism efficacy suggested validity evidence based on relations with other variables. Conclusion The results suggest that the instrument is an appropriate measure of critical consciousness in sport. It is recommended that future efforts focus on estimating further validity evidence and reliability of the CCSS in diverse samples of athletes from different competitive levels, sports coaches, fans, and other key figures within the sports context.